PENANAMAN PENDIDIKAN NILAI-NILAI MULTIKULTURAL DALAM PEMBELAJARAN SEJARAH KELAS XI DI SMA ISLAM BAWARI PONTIANAK - Andari, Desi; Noor, Agus Sastrawan; Firmansyah, Andang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractIndonesia is widely known as a multicultural country. This very complex diversity makes Indonesia a culturally diverse country. Multiculturalism in Indonesia should put aside SARA (ethnicity, religion, race, and between groups). Therefore, a multicultural understanding of diversity must always be applied in the learning process. Through historical education which is related to the formation of national character by prioritizing different cultural values. This study aims to find out and get accurate information about the cultivation of multicultural values education at SMA Islam Bawari Pontianak. This research used qualitative research method with sampling purposive technique. The results showed that cultivation of multicultural values education has been applied in the learning process through historical education by inserting multicultural-based values can create the harmony and communion outside and inside the school environment and the high tolerance attitude of students and other school members.Keywords : Multicultural, Historis Learning, Education